Systematics of oriental termites. No. 7. A new termite, Odontotermes mathadi, from India and the imago of O. meturensis R. & C. (Isoptera: Termitidae). - Roonwal, Mitthan Lal; Chhotani, O. B. (Contributions to Entomology = Beiträge zur Entomologie, 1964)
1. A new species, Odontotermes mathadi, is described from soldiers and workers from southern India (type-locality: Badami, Bijapur Dist., Mysore State). The species belongs to the l0. obesus group', but is the largest. The soldier is separable from its close allies, O. bellahunisensis and O. kapuri, in the shape of the labrum and the position of the mandibular tooth. - 2. The hitherto unknown imago caste of a recently discovered Indian species, Odontotermes meturensis Roonwal & Chhotani (1959, 1960) is described, from imago material (associated with soldiers and workers) from Bangalore, southern India.Nomenclatural Actsmathadi Roonwal & Chhotani, 1964 (Odontotermes), spec. n.